Retrospective evaluation of novel serum inflammatory biomarkers in first-episode psychiatric disorders: diagnostic potential and immune dysregulation - Qiu, Min; Zhang, Chenkai; Zhang, Haiqing; Chen, Hao; Lei, Yingjia; Li, Ping; Zhang, Shaochuan (Frontiers in Psychiatry, 2024)
BackgroundThis study assessed the diagnostic capabilities of eight inflammatory biomarkers in first-episode schizophrenia (SCZ), bipolar disorder (BD), and depression (D), examining their differential expression across these psychiatric disorders. The markers studied include neutrophils/lymphocyte ratio (NLR), aggregate index of systemic inflammation (AISI), systemic immune-inflammation index (SII), systemic inflammation response index (SIRI), lymphocytes/high-density lipoprotein (HDL) ratio (LHR), monocytes/HDL ratio (MHR), neutrophils/HDL ratio (NHR), and platelets/HDL ratio (PHR).MethodsWe conducted a retrospective observational study involving 335 individuals with SCZ, 68 with BD, 202 with D, and 282 healthy controls (C) to evaluate hematologic parameters from untreated patients and controls.ResultsSignificant differences in biomarker levels were found between patient groups and controls. Logistic regression analysis indicated that NHR and MHR (p < 0.001), as well as LHR and NLR (p < 0.01), were predictive factors for SCZ. MHR was a predictive factor for BD (p < 0.05). NHR (p < 0.01) and MHR (p < 0.001) were predictive factors for distinguishing between D and C. The area under the curve (AUC) value of the NHR + MHR + NLR composite index model for the SCZ group was 0.846 (p < 0.001). In the BD group, the AUC value for the MHR was 0.816 (p < 0.001). The D group’s combined AUC value of NHR + MHR was 0.824 (p < 0.001).ConclusionThis study highlights the diagnostic value of inflammatory biomarkers in distinguishing SCZ, BD, and D based on their differential expression.